Pengaruh Penggunaan Koobits terhadap Motivasi, Kemandirian, dan Hasil Belajar Matematika melalui Model Pembelajaran Blended-Learning pada Siswa Kelas V Sekolah Dasar - Maria Imnocensia Rosdewi Taeteti; Agus Santoso (Syntax Corporation Indonesia, 2024)
This research aims to explore the comparison on motivation, independence, and mathematics learning outcomes through technologies integration in mathematics learning process, between students who utilized KooBits (an online learning platform) and those who did not. Involving 66 students from grade 5, the study used a quasi-experimental design. The experimental class consisted of 34 students who used KooBits, while the control class consisted of 32 students. The research instruments included a scoring rubric, a motivation scale, and a learning independence scale. Through a T-test for the mean scores and n-gain scores of motivation, independence, and learning outcomes. The results of the independent sample t-test show that the Sig value for learning outcomes is 0.668 < 0.05, for learning motivation Sig is 0.331 > 0.05, and for learning independence Sig is 0.017 < 0.05. The results showed no significant differences in motivation and learning outcomes, but there were differences in the aspects of learning independence.